History of Kelantan, 1890-1940 - Shahril Talib (Monographs of the Malaysian Branch, Royal Asiatic Society, 1995)
History of Kelantan, 1890-1940 is primarily concerned with the political and administrative development of modern Kelantan under the influence of, first, Siam, and then, Britain.